Multipronged Projects To Improve Flow And Responsiveness In Receiving - Koh, Han Teng (Universiti Sains Malaysia, 2017)
Receiving of a manufacturing facility involves handling of a high variety of items loaded from different suppliers. The process can be complicated as documents have to be processed, quality inspection and test, relabelling, good transportation, warehouse admission and storage, return goods and clearance all happen concurrently. In the absence of proper coordination, receiving can be chaotic and congested, especially during the peak seasons in which inundation of incoming goods from suppliers is common. Another concern lays on the process efficiency in terms of flow and responsiveness, as any delay inevitably expand manufacturing lead time. Based on the strict sense of lean manufacturing, receiving is considered non-value added but necessary process. Empirical studies on industry improvements at receiving are scarce in literature. This research investigated ways to improve receiving process, following the Plan-do-check-act (PDCA) methodology. The improvement led to multipronged endeavours mainly to improve the interdepartmental responsiveness. This research led to the improved flow of materials in BSM’s warehouse, reducing the time for newly received raw materials to be allocated in their final locations in warehouse. This enables sufficient raw materials to be sent into production lines and ensure smoother productions. This research provided the practitioner to have a clearer view towards to flow of materials in the warehouse, as well as determining the possible wastes in the flow of raw materials from receiving process to put away processes (final location).